Linking long noncoding RNAs (lncRNAs) and doping detection. Issue 5 (11th November 2020) - Bonilauri, Bernardo; Dallagiovanna, Bruno
Abstract : In the fight against doping, efficient methods for detecting substances or biomarkers are still being improved. Indirect methods are an interesting alternative for the detection of substances misuse longitudinally. Here we shed lights the long non‐coding RNAs (lncRNAs) as a possible biomarkers due to their characteristics such as tissue‐specific expression and strict regulation.